In Vitro Anthelmintic Activity Of Stem Bark Of Millingtonia Hortensis Linn. - NAGARAJA.M.S; PADMAA. M. PAARAKH (International Journal of Pharma and Bio Sciences, 2011)
The present study was undertaken to evaluate anthelmintic activity of different extracts (petroleum ether, benzene, chloroform, methanol and aqueous extracts) of stem bark of Millingtonia hortensis (Bignoniaceae) against adult earthworm Pheretima posthuma. Piperazine citrate was used as standard reference drug. Among all the extract tested, methanol showed dose dependent anthelmintic and better activity in comparison with reference standard. Chloroform and benzene extracts at 20 mg/ml concentration also showed similar activity in comparison with piperazine citrate at dose of 60 mg/ml. Aqueous extract was not at all active. Preliminary phytochemical screening revealed the presence of steroids, flavonoids and tannins in different extracts.